2020
DOI: 10.1161/hypertensionaha.119.13866
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Steroid Biomarkers for Guiding Primary Aldosteronism Subtyping

Abstract: Adrenal vein sampling (AVS) is required to distinguish unilateral from bilateral aldosterone sources in primary aldosteronism (PA), and cortisol is used for AVS data interpretation, but cortisol has several pitfalls. In this study, we present the utility of several other steroids in PA subtyping, both during AVS, as well as in peripheral serum. We included patients with PA who underwent AVS at University of Michigan between 2012 and 2018. We used mass spectrometry to simultaneously quantify 17 steroids in adre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 30 publications
4
34
0
Order By: Relevance
“…Subsequently, Eisenhofer et al demonstrated a decreased discriminative ability of 18OHF and 18oxoF between APAs and BHA among European PA population, whereas 80% of PA patients were correctly subclassified into the PA subtypes by measurement of 12 steroids employing liquid chromatography–mass spectrometry [ 134 ]. Similar results were also reported by an American PA cohort, in which four subgroups based AVS results before and after cosyntropin injection had different steroid profiles in peripheral serum [ 55 ]. All those studies indicate that steroid profiling in peripheral blood could circumvent AVS in patients with BHA after PA confirmation, although the used steroids varied among the studies.…”
Section: Recent Advance In Simplifying the Pa Diagnostic Flowsupporting
confidence: 87%
See 2 more Smart Citations
“…Subsequently, Eisenhofer et al demonstrated a decreased discriminative ability of 18OHF and 18oxoF between APAs and BHA among European PA population, whereas 80% of PA patients were correctly subclassified into the PA subtypes by measurement of 12 steroids employing liquid chromatography–mass spectrometry [ 134 ]. Similar results were also reported by an American PA cohort, in which four subgroups based AVS results before and after cosyntropin injection had different steroid profiles in peripheral serum [ 55 ]. All those studies indicate that steroid profiling in peripheral blood could circumvent AVS in patients with BHA after PA confirmation, although the used steroids varied among the studies.…”
Section: Recent Advance In Simplifying the Pa Diagnostic Flowsupporting
confidence: 87%
“…The interpretation of AVS results could be influenced by sampling conditions and respective cut-off values for laterality index [ 54 ]. Based on those different procedures, Turcu et al described discordant results of AVS between before and after cosyntropin stimulation [ 55 ]. Among 103 cases where adrenal veins were appropriately cannulated, only 69 cases (67.0%) had consistent lateralization of hyperaldosteronism, unilateral or bilateral, between pre- and post-cosyntropin injection, whereas the remaining 34 cases (33.0%) had different lateralization after cosyntropin stimulation compared to that of baseline: from unilateral to bilateral or the opposite change [ 55 ].…”
Section: Epidemiology Of Pamentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, even with multi-steroid panels measured in peripheral blood samples, the distinction between cases classified as unilateral or bilateral based on baseline AVS data alone was poor (AUC of 0.586). In contrast, the same 17-steroid panel measured in peripheral blood performed better in distinguishing patients with consistent unilateral or bilateral PA subtyping results based on pre-and post-cosyntropin stimulation AVS data (AUC of 0.768 with steroids measured at baseline, and 0.907 with steroids measured after cosyntropin-stimulation) [65]. Our results emphasize that PA subtypes are difficult to dichotomize (▶Fig.…”
Section: Steroid Profiling As a Tool For Pa Subtypingmentioning
confidence: 63%
“…In a recent study, we used LC-MS/MS to compare the steroid profiles between stratified PA subtypes [65]. Out of 103 patients with valid AVS data both prior to and following cosyntropin administration, 20 patients met criteria for unilateral PA only at baseline and other 14 patients showed lateralization only after cosyntropin stimulation.…”
Section: Steroid Profiling As a Tool For Pa Subtypingmentioning
confidence: 99%